Model intervensi partisipatif berbasis masyarakat (CBPI) dalam pendampingan kader kesehatan jiwa - Kurniawati, Ratna; Anisah, Retno Lusmiati; Yuliastuti, Anie (Nur Science Institute, 2025)
Strengthening the capacity of mental health cadres is a crucial strategy in community-based health services. This community service program aims to implement a Community-Based Participatory Intervention (CBPI) approach to assist cadres in improving their literacy, skills, and active role in mental health services. Activities were conducted in Ngemplak Hamlet, encompassing problem identification, cadre training, community education, and participatory evaluation. Results demonstrated increased cadre knowledge and community engagement on mental health issues. CBPI has proven to be an effective, participatory, and sustainable approach. The activities were carried out for 7 months from January to July 2025. The CBPI method has proven effective in increasing knowledge, encouraging behavioral change, and strengthening rural community resources in addressing mental health issues. In conclusion, cadre readiness to provide support has increased, the number of people concerned with mental health issues has expanded and become more active, coordination between cadres has begun to develop, and direct interventions by cadres with ODGJ patients have been well-implemented, such as home visits, referrals, and social outreach.